Black transparency : the right to know in the age of mass surveillance - Metahaven (Design studio) (Berlin : Sternberg press, 2015)
Black transparency is an involuntary disclosure of secrets against a backdrop of systematic online surveillance, as large parts of contemporary life move into the digital realm. Black transparency, as a radical form of information democracy, has brought forward a new sense of unpredictability to international relations, and raises questions about the conscience of the whistleblower, whose personal politics are now instantly geopolitical. Empowered by networks of planetary-scale computation, disclosures today take on an unprecedented scale and immediacy. Difficult to contain and even harder to prevent, black transparency does not merely create openness, order, and clarity; rather, it triggers chaos, stirring the currents of a darker and more mercurial world. Metahaven was founded in 2007 by Vinca Kruk and Daniel van der Velden. In Black Transparency - part essay, part fanzine - Metahaven embark on a journey of subversion, while examining transparency's intersections with design, architecture, and pop culture, as well as its ability to unravel the circuitry of modern power.
A Google executive once said: "If you want to liberate a society just give them the Internet." But how does one liberate a society that already has the Internet? Publicly, modern government adheres to the twin ideals of institutional transparency and personal privacy. In reality, while citizens are subjected to mass surveillance, government practice goes unchecked. A new generation has taken to the Internet to defend the right to governance without secrets. From Bradley Manning and WikiLeaks to LulzSec and Anonymous, from the Icelandic Modern Media Initiative to the revelations of Edward Snowden, a coalition is breaking through the secrecy that lies at the core of the modern state. The story gets more complex when open government is contrasted with black transparency, and when a geopolitical rift between the West and Russia becomes the dividing line for whistleblowers and transparency activists seeking refuge. What is transparency for one may be propaganda for the other.
boek
Keywords: Internet -- politiska aspekter; Internet -- sociala aspekter; Massmedia; Internet -- Political aspects; Internet -- Social aspects; Freedom of information; Mass media and culture; Design -- Political aspects; Popular culture -- Political aspects; Architecture -- Political aspects; Architecture -- Political aspects; Design -- Political aspects; Freedom of information; Internet -- Political aspects; Internet -- Social aspects; Mass media and culture; Popular culture -- Political aspects; Mass media